Optimization Of Zinc Sulfate Application To Improve The Quantity And Quality Of Rice Crops (Oryza Sativa L.) - Nurhidayanti Nurhidayanti; Ayatilla Ar-Raufah Rahmayadi; Evelin Gumulia; Tety Suciaty (Jurnal Agrosci, 2025)
Background. Zinc (Zn) is known as an important micronutrient for plants, playing a significant role in optimizing growth, yield, and the quantity and quality of rice plants. Aims. This study focuses on determining the optimal dose of Zinc Sulfate Heptahydrate (ZnSO4) fertilizer in response to the growth and yield of rice plants, as well as the Zn content in rice. Methods. This study was conducted in Kaliaren, Kuningan, from May to August 2025. This study used a single-factor randomized block design (RAK) with 5 dose treatments and 5 replicates. The data will be processed using Analysis of Variance (ANOVA) and Duncan's multiple range test (DMRT). Conclusion. The results of this study indicate that 8 kg/ha of zinc sulfate heptahydrate fertilizer is the optimal dose for increasing the quantity and quality of rice (Oryza sativa L.) yields.